Development of a Functional Schwann Cell Phenotype from Autologous Porcine Bone Marrow Mononuclear Cells for Nerve Repair - Michael J. Rutten; Michael Ann Janes; Ivy R. Chang; Cynthia R. Gregory; Kenton W. Gregory (Stem Cells International)
Adult bone marrow mononuclear cells (BM-MNCs) are a potential resource for making Schwann cells to repair damaged peripheral nerves. However, many methods of producing Schwann-like cells can be laborious with the cells lacking a functional phenotype. The objective of this study was to develop a simple and rapid method using autologous BM-MNCs to produce a phenotypic and functional Schwann-like cell. Adult porcine bone marrow was collected and enriched for BM-MNCs using a SEPAX device, then cells cultured in Neurobasal media, 4 mM L-glutamine and 20% serum. After 6–8 days, the cultures expressed Schwann cell markers, S-100, O4, GFAP, were FluoroMyelin positive, but had low p75(NGF) expression. Addition of neuregulin (1–25 nM) increased p75(NGF) levels at 24–48 hrs. We found ATP dose-dependently increased intracellular calcium [Ca2+]i, with nucleotide potency being UTP=ATP>ADP>AMP>adenosine. Suramin blocked the ATP-induced [Ca2+]i but α, β,-methylene-ATP had little effect suggesting an ATP purinergic P2Y2 G-protein-coupled receptor is present. Both the Schwann cell markers and ATP-induced [Ca2+]i sensitivity decreased in cells passaged >20 times. Our studies indicate that autologous BM-MNCs can be induced to form a phenotypic and functional Schwann-like cell which could be used for peripheral nerve repair.